PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA PAPAN JURANG UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG OPERASI BILANGAN CACAH DI SEKOLAH DASAR - Humola, Apriana; Rifda Mardian Arif; Andi Marshanawiah; Gamar Abdullah; Nur Sakinah Aries (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study addresses the research question: “Can the implementation of a Problem-Based Learning (PBL) model supported by the ‘Papan Jurang’ instructional media improve the arithmetic skills of third-grade elementary school students in whole number operations?” The objective of this study is to enhance students’ numeracy skills through the application of the Problem-Based Learning model assisted by the Papan Jurang media, particularly in addition and subtraction of whole numbers among third-grade elementary school students. This research employed a Classroom Action Research (CAR) design. Data collection techniques included tests, observations, and documentation. The results of the preliminary observation indicated that only 20% of students (2 students) achieved mastery learning. In the first cycle, learning mastery improved to 55% (5 students), although it did not yet meet the classical completeness criterion of 80%. After proceeding to the second cycle, a significant improvement was observed, with learning mastery reaching 89% (8 students). Therefore, it can be concluded that the implementation of the Problem-Based Learning model supported by the Papan Jurang media significantly improves the arithmetic skills of third-grade elementary school students.